The Effect of Organizational Culture and School Climate on the Quality of Education Services and Their Implications on the Quality of the Graduates - Herdianto Wahyu Pratomo (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study was conducted in Islamic Junior High school (MTs) throughout sub-district of Kadipaten, Majalengka, with a focus of research on aspects of organizational culture, school climate, quality of education services, and quality of graduates. This study aims at descriptively analyzing the organizational culture, school climate, quality of education services, and quality of graduate students. Moreover, it also aims at verily analyzing the effect of organizational culture and school climate on the quality of education services in Islamic Junior High school (MTs) throughout sub-district of Kadipaten, Majalengka, both partially and simultaneously, and the effect of the quality of educational services on the quality of graduates. The research method used is descriptive and verification survey methods. Data collection is carried out primarily and secondarily. The sampling method used is proportional sampling using the Slovin formula. The analysis technique used is path analysis. The results of this study indicated that the organizational culture was categorized as good, yet there were still weaknesses in the aspect of the teachers' aggressiveness. The school climate was considered good, yet there were still weaknesses in the aspect of the institutional environment. The quality of education services was quite good, yet there were still weaknesses in the aspect of responsiveness. The quality of graduates was categorized as good, yet there were still weaknesses in the aspects of affective abilities. The results of the verification study showed the organizational culture and school climate had a positive and significant effect on the quality of education services, as well as the quality of education services had a positive and significant effect on the quality of student graduates.